Factors Associated With The Covid-19 Vaccination Participation In The Area Of Noyontaan Primary Healthcare Center Pekalongan City - Farras Azizah (Journal of International Multidisciplinary Research, 2024)
This research article aims to analyze factors associated to participation in the COVID-19 vaccine in the Noyontaan Primary Healthcare Center area, Pekalongan City. This research is a type of analytical research and the design used in this research is case control. This research uses primary data and secondary data. Samples were 46 cases and 46 controls using random sampling technique. The instrument used was a structured questionnaire. Data were analyzed with chi-square test. Results showed that knowledge (OR=4.136; 95% Cl=1.692-10.110), perception towards vaccine safety (OR=2.46; 95% Cl=1.055-5.736) were associated to COVID-19 vaccine participation. Meanwhile attitude (OR=1.312; 95% Cl=0.569-3.026), history of comorbid disease (OR=0.54; 95% Cl=0.236-1.237), perception towards AEFI (OR=0.825; 95% Cl=0.35-1.949), perception towards COVID-19 impact (OR=1.192; 95% Cl=0.524-2.709) were not were associated to COVID-19 vaccine participation.